2013
DOI: 10.1007/s00330-013-2856-4
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary observations and clinical value of lipid peak in high-grade uterine sarcomas using in vivo proton MR spectroscopy

Abstract: • High lipid peak on MR spectroscopy is suggestive of uterine sarcomas. • Lipid peak is observed in both viable and necrotic areas in sarcomas. • MR spectroscopy may be useful in distinguishing uterine sarcomas from benign leiomyomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Interestingly, a recent study reported significantly lower choline concentration in carcinosarcomas than in endometrioid carcinomas (18). Tumor necrosis is reportedly more pronounced in non-endometrioid endometrial cancers (30) and tumors with necrosis are known to exhibit low choline concentrations, putatively due to the low numbers of viable tumor cells (31). Theoretically, microscopic tumor necrosis could, thus, explain the relatively low choline concentration observed in non-endometrioid tumors compared with grade 3 endometrioid tumors in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study reported significantly lower choline concentration in carcinosarcomas than in endometrioid carcinomas (18). Tumor necrosis is reportedly more pronounced in non-endometrioid endometrial cancers (30) and tumors with necrosis are known to exhibit low choline concentrations, putatively due to the low numbers of viable tumor cells (31). Theoretically, microscopic tumor necrosis could, thus, explain the relatively low choline concentration observed in non-endometrioid tumors compared with grade 3 endometrioid tumors in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, Takeuchi et al. also reported that high-grade malignant uterine tumors may often show massive necrosis and may cause low choline concentration due to the decrease in viable tumor cells, and the presence of high lipid peaks may be useful in distinguishing uterine sarcomas from benign leiomyomas (26). Lipid peaks arising from triglycerides and cholesterol esters in neutral lipid droplets may be observed both in viable and necrotic areas of the tumor, and are considered to be important biomarkers in the diagnosis of malignant tumors (27).…”
Section: Discussionmentioning
confidence: 99%
“…In studies regarding the uterine tumors, Okada et al (59) and Celik et al (60) found that choline was present in benign and malignant lesions, while Takeuchi et al (61) reported that malignant lesions have higher levels of choline, and a cutoff of 7 mmol might distinguish between them with 83% sensitivity and 93% specificity. Lipid peaks also showed promising results for distinguishing uterine sarcomas from benign leiomyomas (62). In the case of tumors of the cervix, unfortunately choline is present in normal and tumor tissue without any detectable differences between them (58,(63)(64)(65)(66)(67).…”
Section: Genitourinary Tumors (Excluding Prostate)mentioning
confidence: 92%